2019
DOI: 10.1007/s13300-019-0580-z
|View full text |Cite
|
Sign up to set email alerts
|

Incretin-Based Antihyperglycemic Agents for the Management of Acute Ischemic Stroke in Patients with Diabetes Mellitus: A Review

Abstract: Diabetes mellitus (DM) is a major risk factor for ischemic stroke. Moreover, patients with DM suffer more severe strokes and have worse functional outcome following an acute stroke than patients without DM. In this context, data from animal studies and emerging evidence from clinical studies suggest that incretin-based antihyperglycemic agents might exert beneficial effects in patients with DM who suffer ischemic stroke. It appears that these agents exert neuroprotective actions that might both reduce infarct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A recently published review in which several preclinical studies were examined, it was concluded that using GLP-1 agonists improve functional outcome after ischemic stroke. It’s unknown whether these results are valid for humans in clinical practice[82].…”
Section: Cardiovascular Outcomes Of Incretin-based Therapy In T2dmmentioning
confidence: 99%
“…A recently published review in which several preclinical studies were examined, it was concluded that using GLP-1 agonists improve functional outcome after ischemic stroke. It’s unknown whether these results are valid for humans in clinical practice[82].…”
Section: Cardiovascular Outcomes Of Incretin-based Therapy In T2dmmentioning
confidence: 99%
“…Diabetes mellitus mainly consists of two clinical forms, Type 1 and Type 2 diabetes, especially the latter accounting for about 90 % of all diabetics worldwide. [1] Type 2 diabetes is a chronic metabolic disorder featuring hyperglycemia, [2] which can also cause other disease complications, [3] e. g., stroke, renal, cardiac and hepatic disorders. [4,5] In 2019, about 403 million diabetics were diagnosed worldwide with one death every five seconds, and the number of patients was estimated to be 700 million by 2045.…”
Section: Introductionmentioning
confidence: 99%